Seismogram Analysis of C052198B Earthquake, Minahasa at Observatory Stations in Australia - Bagus Jaya Sentosa (Institute for Research and Community Services (LPPM) ITB, 2012)
The earth structure between the Minahasa earthquake, coded as C052198B, and observatory stations in Australia has been investigated through analysis in the time domain of three-component seismograms. The synthetic seismograms are constructed from an earth model, the CMT solution of the earthquake and station locations. The calculation is based on the GEMINI method, and the corner frequency is set at 20 mHz. Using deconvolutions of the station instruments responses, the measured and synthetic seismogram can be compared with the same units. The seismogram comparison indicates discre-pancies between recorded data and synthetic seismograms calculated from the anisotropic PREM model, in the travel times of Rayleigh and Love surface wave, as well as the S and core reflected ScS and ScS2 body waves. Discrepancies of Love wave travel time and the number of oscillations are explained by changes in the crustal velocity model and by setting the positive gradient of bh in the upper mantle. While for Rayleigh waves and arrival times of body waves, corrections to the zero order coefficients of b are needed at layers in the mantle. The interpretation of the results of the waveform analyses indicates strong anisotropy in the upper mantle. The anisotropy also occurs, to a lesser extent, at layers beneath the upper mantle.